The Impact of The Covid-19 Pandemic On Increasing Poverty - Rina Simarmata; Dinda Khairul Apriladini; Santi Fitriani Munthe (Outline Publisher, 2026)
Purpose: This study analyzes the impact of the Covid-19 pandemic on poverty levels in Indonesia by examining positive Covid-19 cases, life expectancy, income inequality, and GRDP per capita across 34 provinces in 2020. Methods: A quantitative approach with multiple regression analysis was applied using provincial-level data. Independent variables included positive Covid-19 cases, life expectancy, Gini Ratio, and GRDP per capita, with poverty as the dependent variable. Results: The findings show that positive Covid-19 cases significantly increase poverty, where each additional case raises the number of poor people by 0.0087. Life expectancy also has a positive effect, with every additional year increasing poverty by 130.11932. Income inequality worsens poverty, as a 1% increase in the Gini Ratio adds 533.7175 poor individuals. In contrast, GRDP per capita reduces poverty, with every Rp. 1000 increase lowering the number of poor people by 0.0234. Conclusions: The pandemic exacerbates poverty through health and inequality factors, while economic growth helps alleviate it. Policies should focus on controlling Covid-19, reducing inequality, and fostering inclusive growth. Originality/value: This study uniquely integrates health and economic variables in one model to explain poverty dynamics during a pandemic crisis in Indonesia.